2015
DOI: 10.3748/wjg.v21.i45.12981
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of hepatoma with mantle cell lymphoma in a hepatitis B carrier

Abstract: The coexistence of hepatocellular carcinoma (HCC) and non-Hodgkin's lymphoma (NHL) in the liver is rare. Reports show that these patients have cirrhotic livers or hepatitis virus infections before they develop HCC and NHL. We present a patient with hepatitis B virus infection who was transferred to our hospital with a newly detected liver mass; abdominal computed tomography examination showed one hypodense mass of 7 cm in diameter and multiple mesenteric and mediastinal lymph nodes. A liver tumor biopsy showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The coexistence of lymphomas and HCC has been mostly reported in clinical patients infected with hepatitis virus [ 67 , 68 ], while cohort studies and case–control studies have consistently reported that the increased risks of both HCC and lymphoma are associated with infection of HCV or HBV [ 69 – 72 ]. A Danish HCV cohort (DANVIR) cohort study of liver cancer and non-Hodgkin lymphoma was performed in HCV-infected patients [ 73 ].…”
Section: Secondary Lymphomasmentioning
confidence: 99%
“…The coexistence of lymphomas and HCC has been mostly reported in clinical patients infected with hepatitis virus [ 67 , 68 ], while cohort studies and case–control studies have consistently reported that the increased risks of both HCC and lymphoma are associated with infection of HCV or HBV [ 69 – 72 ]. A Danish HCV cohort (DANVIR) cohort study of liver cancer and non-Hodgkin lymphoma was performed in HCV-infected patients [ 73 ].…”
Section: Secondary Lymphomasmentioning
confidence: 99%